Calidad de vida del cuidador familiar y grado de dependencia del paciente Adulto Mayor con Enfermedades Crónicas en el programa de atención domiciliaria (PADOMI) del Hospital Essalud II – 2 Tarapoto. Agosto a Diciembre 2016 - Arévalo Villa, Barbara Dayanara (2017)
The main objective of the following research was to determine the relationship between the quality of life of family caregivers and the degree of dependence of older patients with chronic diseases from PADOMI program at EsSalud 11-2 Hospital, Tarapoto- Peru, and August- December 2016. lt is a non-experimental study with a correlational descriptive design of a cross sectional type, the sample consisted of 54 family caregivers. The results were as follows: The most relevant socio demographic characteristics of family caregivers are: 35.2% are caregivers between ages 51 to 66, 75.9% are female, 50% have higher education and 46.3% are children. The quality of life of family caregivers according to the dimensions are: Emotional well-being 46.3% presents regular quality of life, interpersonal relations 48.1% present a regular quality of life and physical well-being 57.4% present a regular quality of life. There is a severe dependence rate of 42.6% in elderly patients of the Home Care Program (PADOMI). In conclusion, there is no significant relationship between the family quality of the caregiver and the degree of dependence of the older patients with chronic diseases from PADOMI program of the Tarapoto Hospital EsSalud 11- 2 with chi - 0.401 square